The Philosophical aspects of cybernetic modelling in methodology of sustainable development policy - Haliniak, Marek (Studia Ecologiae et Bioethicae, 2003)
The article deals with the experience and results of attempts aimed at using cybernetic system methods for modeling the policy of sustainable development. The analysis is made from the ecophilosophical perspective. Cybernetics is presented as the sub-philosophical, general, and inter-disciplinary science with a high level of influence on the process of policy-making and policy-makers. However, the barriers of philosophy and cybernetics in that respect are strictly connected with the limits of philosophy. The question concerns the problem of transferring the ideas into practice by the method of cybernetic modeling. Whereas the conceptual model should reflect the objective reality it should be based on some general, politically accepted ideas. This necessity is obvious because of the link between the basic axioms of a given model with the general results generated by it. The author analyses the possibility of appliance the Sage-Michnowski model as the instrument for planning the sustainable development policy as the interrelated social, economic, and ecological system.